Crop production growth in different agro-ecological zones of Bangladesh (Journal of the Bangladesh Agricultural University, 2010)
The purpose of this study is to evaluate the progress and regional variations of crop production in Bangladesh. The secondary data were used and collected for the years 1980-81 to 2002-03 from the ‘Statistical Yearbooks of Bangladesh', ‘Yearbook of Agricultural Statistics' and population census of different years. The study was conducted during the period from September 2006 to February 2008. An analysis was done for twelve mutually exclusive agro-ecological zones by assigning various indicators of crop sector development. The remarkable progress of rural literacy rate, ratio of agricultural workers to population, number of farmer's co-operative societies and per capita regional domestic agricultural products in two decades was observed in different regions. Wide disparities in the level of crop sector development had been observed across the regions. The overall results reveal that some of the regions are in better positions in respect of socioeconomic progress, land use pattern, input use, growth performance of HYV rice and food-grains production. The developed regions were 'Old Himalayan Piedmont Plain and Tista Floodplain', 'Karatoya Floodplain and Atrai Basin', 'Brahmaputra-Jamuna Floodplain' and 'Middle Meghna River Floodplain' on the basis of land utilization pattern, input use and food-grains production. Analysis of regional disparities reveals that 'Sylhet Basin and Surma-Kusiyara Floodplain', 'Greater Dhaka', 'Middle Meghna River Floodplain' and 'Lower Meghna River and Estuarine Floodplain' regions has developed remarkably in the last twenty years. Keywords: Crop production; Development indicator; Growth performance; Regional variation DOI: 10.3329/jbau.v7i2.4746 J. Bangladesh Agril. Univ. 7(2): 351-360, 2009